Hubungan Kepatuhan Minum Tablet Fe dengan Anemia Ibu Hamil di Wilayah Kerja Puskesmas Grabag II Kabupaten Magelang - Fatimah Sari; Yustina Ananti; Enywati Iris Tombokan (LPPM STIKES Guna Bangsa, 2017)
Background : Anemia in pregnant women in a national problem. In Indonesia, the incidence of anemia in pregnancy is quite high. Anemia prevention program does is provide iron tablet that preparations Fe. How to consume tablets Fe followed by respondents as important to follow the advice given by the researchers then the tendency will increase in hemoglobin levels as expected. Objective : Given the relationship between adherence Fe tablets in pregnant women with anemia Puskesmas Grabag II Magelang regency. Methods : This study is a correlational research analytic, using a cross- sectional survey design. The sampling technique used was purposive sample of the number of samples in this study were 134 respondents. Results : There was a relationship adherence Fe tablets with maternal anemia status in Puskesmas Grabag II Magelang regency with p value of 0.000 (0.000 < 0.05) and the relationship is strong enough that the value of the Contingency Coefficient 0.556. Conclusion : There is a relationship adherence Fe tablets with maternal anemia status.